PENGEMBANGAN KURIKULUM PENDIDIKAN LINGKUNGAN PERSPEKTIF ISLAM DALAM PENDIIDKAN AGAMA ISLAM: A SYSTEMATIC LITERRATUR REVIEW - Asmara Hayati; Ahmad Saeful Ahyar; Zulhanannan; Ali Murtadho; Baharudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The ongoing environmental crisis demands a serious role of education in fostering continuous environmental awareness among students. Environmental education implemented in schools has largely been oriented toward a scientific approach and has insufficiently addressed Islamic values and spiritual dimensions. Islam, as a holistic religion governing the relationship between humans and nature, offers a strong ethical foundation for environmental stewardship. This article aims to analyze and map the development of an Islamic-based environmental education curriculum within Islamic Religious Education (IRE) at the junior secondary school level through a Systematic Literature Review approach. The study examines 28 scholarly articles published between 2021 and 2025, which were analyzed using the PRISMA protocol. The findings reveal four main themes: theological and ethical foundations of environmental education, integration of environmental education into the IRE curriculum, the pedagogical role of teachers and ecological learning models, and challenges as well as future directions for the development of environmentally oriented IRE curricula. These findings emphasize that the development of an environmentally based IRE curriculum should be conducted in an integrative,systematic, and sustainable manner grounded in Islamic values.